Axial loading during MRI induces significant T2 value changes in vertebral endplates—a feasibility study on patients with low back pain - Hanna Hebelka; Andreia Miron; Izabela Kasperska; Helena Brisby; Kerstin Lagerstrand (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background The function of the endplate (EP) is the most important factor influencing nutritional supply to the avascular intervertebral disc (IVD). It is desired to have a non-invasive method to assess functional EP characteristics in vivo. Assessment of functional EP characteristics is important in order to understand its relation to IVD degeneration, which in turn might deepen the understanding of the pathophysiology behind low back pain (LBP). It was hypothesized that, by comparing quantitative MRI of EPs performed with conventional supine MRI (unloaded MRI) with axial loading during MRI (alMRI), dynamical properties of the EP can be displayed. The aim was therefore to investigate the feasibility of axial loading during MRI (alMRI) to instantaneously induce quantitative EP changes. Methods T2 mapping of 55 vertebral EPs (L1-S1) in five LBP patients was performed during conventional supine MRI (unloaded MRI) and subsequent alMRI. With T2 mapping, the cartilaginous EP and bony EP cannot be separated; hence, the visualized EP was termed EP zone (EPZ). Each EPZ was segmented at multiple midsagittal views, generating volumetric regions of interest. EPZs demonstrating signal inhomogeneity and/or adjacent Modic changes (MC) were termed abnormal EPZs. EPZ mean T2 values were compared between unloaded MRI and alMRI, and their relationship with abnormal EPZs was determined. Results alMRI induced significantly higher (p = 0.01) EPZ mean T2 values compared with unloaded MRI. Significantly higher mean T2 values were seen in inferior EPZs compared with superior EPZs, both with unloaded MRI (35%, p < 0.001) and with alMRI (26%, p = 0.04). Significant difference between unloaded MRI and alMRI was seen in normal (p = 0.02), but not in abnormal EPZs (p = 0.5; n = 12). Conclusions alMRI induces changes in human EPZ characteristics in vivo. The T2 value significantly increased in normal EPZs, with lack of such in abnormal EPZs. Combining T2 mapping with alMRI provides a clinical feasible, non-invasive method with potential to reveal biochemical behavioral patterns, thus adding another dimension of the EPZs characteristics compared with information obtained with solely unloaded MRI.